Monolithic ceramics: Effect of finishing techniques on surface properties, bacterial adhesion and cell viability - Dal Piva, A. M.O. [UNESP]; Contreras, L. P.C. [UNESP]; Ribeiro, F. C. [UNESP]; Anami, L. C. [UNESP]; Camargo, S. E.A. [UNESP]; Jorge, A. O.C. [UNESP]; Bottino, M. A. [UNESP] (Operative Dentistry, 2018)
Introduction: This study evaluated the morphology, biofilm formation, and viability of human gingival fibroblasts in contact with two monolithic ceramics after two different finishing techniques: polishing or glazing. For this, 92 blocks (4.5 × 4.5 × 1.5 mm) of each ceramic were made using high translucency zirconia partially stabilized by yttrium (YZHT) and lithium silicate reinforced by zirconium (ZLS). Methods and Materials: Blocks were sintered and then divided into glazing (g) or polishing (p) surface finish. Surface roughness (Ra and RSm) was evaluated through a contact rugosimeter and profilometry. Specimens were contaminated for heterotypic biofilm formation with Streptococcus mutans, Streptococcus sanguinis and Candida albicans for 16 hours. Biofilm was quantified by counting the colony forming units (CFU/mL) and analyzed by scanning electron microscopy (SEM). Fibroblast viability was evaluated by MTT assay. Surface free energy (SFE) was also determined. Roughness data were evaluated using nonparametric tests, while SFE, MTT and CFU results were evaluated by analysis of variance and Tukey test, and MTT data were also submitted to ttest (all, α=0.05). Results: Results showed that polished samples presented a lower high profile mean (p<0.001); however, YZHTg presented less space between defects (p=0.0002). SFE showed that YZHT presented higher SFE than ZLS. Profilometry evidenced more homogeneity on polished surfaces. The interaction of finishing technique and microorganisms influenced the CFU (p=0.00). MTT assay demonstrated initial severe cytotoxic behavior for polished surfaces. SEM images showed homogeneous surfaces, except for glazed YZHT. Conclusion: Glazed surfaces have a greater roughness and tend to accumulate more biofilm. Polished surfaces have higher SFE; however, they are temporarily cytotoxic.